Development of Soy-Based Meat Analogues via Wet Twin-Screw Extrusion: Enhancing Textural and Structural Properties Through Whole Yeast Powder Supplementation - Shikang Tang; Yidian Li; Xuejiao Wang; Linyan Zhou; Zhijia Liu; Lianzhou Jiang; Chaofan Guo; Junjie Yi (Foods, 2025)
Amid growing global concerns about environmental sustainability and food security, plant-based meat substitutes have emerged as a promising alternative to conventional meat. However, current formulations, especially those based on soy protein isolate (SPI) often fail to replicate the desired texture and structural integrity. To address this limitation, this study aimed to evaluate the use of whole yeast powder (WYP) combined with SPI for producing plant-based meat analogues via high-moisture extrusion. Seven groups were designed: a control group with 0% WYP, five treatment groups with 5%, 10%, 20%, 30%, and 40% WYP, and one reference group containing 20% yeast protein powder (YPP). Although lower in protein content than yeast protein powder (YPP), whole yeast powder exhibits superior water-binding capacity and network-forming ability owing to its complex matrix and fiber content. At a 20% inclusion level, whole yeast powder demonstrated a higher fibrous degree (1.84 ± 0.02 vs. 1.81 ± 0.04), greater hardness (574.93 ± 5.84 N vs. 531.18 ± 17.34 N), and increased disulfide bonding (95.33 ± 0.92 mg/mL vs. 78.41 ± 0.78 mg/mL) compared to 20% YPP. Scanning electron microscopy (SEM) and low-field nuclear magnetic resonance (LF-NMR) revealed that whole yeast powder facilitated the formation of aligned fibrous networks and enhanced water binding. Fourier transform infrared spectroscopy (FTIR) confirmed an increase in β-sheet content (0.267 ± 0.003 vs. 0.260 ± 0.003), which contributed to improved protein aggregation. Increasing the WYP content to 30–40% led to a decline in these parameters, including a reduced fibrous degree (1.69 ± 0.06 at 40% WYP) and weakened molecular interactions (p < 0.05). The findings highlight 20% WYP as the optimal substitution level, offering superior textural enhancement and fibrous structure formation compared to YPP. These results suggest that WYP is not only a cost-effective and processing-friendly alternative to YPP but also holds great promise for scalable industrial application in the plant-based meat sector. Its compatibility with extrusion processes and ability to improve sensory and structural attributes supports its relevance for sustainable meat analogue production.